Development of Interactive Learning Media Based on Augmented Reality for Solid Geometry Concepts - Lestari, Wahyu; Dafik, Dafik (JDIME: Journal of Development and Innovation in Mathematics Education, 2025)
This study aims to develop an interactive learning medium based on Augmented Reality (AR) for teaching three-dimensional geometric shapes to junior high school students. The medium was designed to enhance students’ understanding of geometric concepts, particularly in terms of spatial visualization. The research employed a development approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process involved validation by content and media experts, as well as trials conducted with students to evaluate their responses and the medium’s effectiveness. The results indicated that the developed AR learning medium was highly valid, with a material validity score of 94.5% and a media design validity score of 91.3%. Student response questionnaires revealed that 93.7% of students felt the medium helped them better understand the concepts of three-dimensional figures, while 89.1% stated that the medium made learning mathematics more engaging and enjoyable. Additionally, the average pretest score was 61.7, which increased to 84.2 in the posttest. A paired t-test showed a significance value of p < 0.01, indicating that the improvement in learning outcomes was statistically significant. The AR learning medium was thus proven to be valid and effective in assisting students in visualizing complex geometric objects, as well as making the learning process more engaging and interactive. Consequently, this study recommends the use of AR as an effective alternative learning tool to enhance students' mathematical understanding at the junior high school level.